1) Multiply the two equations by appropriate values to make the coefficients of x or y terms in both equations equal. In this case, the coefficients of x in the first equation and the second equation are already the same (3 and 6, respectively), so there is no need to multiply any equation in this case. However, the coefficients of y in the first equation and the second equation are different, so you need to multiply the first equation by 2 and the second equation by 4 to make the coefficients of y terms equal.
2) After multiplying, you will have the following equations:
First equation: 6x + 8y = 96
Second equation: 24x + 8y = 240
3) Now, you can subtract the first equation from the second equation to eliminate the y term.
24x + 8y - (6x + 8y) = 240 - 96
18x = 144
4) Simplify and solve for x:
18x = 144
x = 8
5) Substitute the value of x back into either of the original equations to solve for y. Let's use the first equation:
3x + 4y = 48
3(8) + 4y = 48
24 + 4y = 48
4y = 48 - 24
4y = 24
y = 6
6) Therefore, the solution to the system of equations is x = 8, y = 6.
3x+4y=48 6x+2y=60
To solve this system, you could do the following steps:
1 answer